DIGITAL ASSISTANCE AND MARKETING STRATEGY FOR OTAK-OTAK BANDENG AMANAH MSMEs COMPETITIVENESS - Purnama, Chamdan; Fatmah, Dinda; Rahmah, Mirhamida; Maulida, Elly Istiana (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia continue to grow positively, with government support helping to revive the economy since the Covid-19 pandemic. To further MSME development, a community engagement program was conducted to provide guidance and solutions for the challenges faced by the Otak-Otak Bandeng Amanah business in Mojokerto. The study used a descriptive research method with a qualitative approach, collecting data through semi-structured interviews, observation, and social media analysis of Otak-Otak Bandeng Amanah. Key challenges identified included limited local awareness of the business, difficulty for new customers to locate it, less appealing product photos on GrabFood and GoFood, and the absence of cashless payment options. Implemented solutions included expanding customer reach through Instagram, Facebook, and TikTok promotions, creating banners and signage, improving product photos, and providing QRIS for cashless payments. Recommendations included ongoing mentoring for other businesses to optimize digital media management.